Designing Lectora Inspire-Based Application as Interactive Multimedia for Teaching Vocabulary of Recount Text - Yovie Anggara Saputra; Rahayu Apriliaswati; Urai Salam (FOSTER: Journal of English Language Teaching, 2021)
This research aimed to design an appropriate interactive multimedia to support teaching vocabulary of recount texts to tenth-grade students of MAN 2 Pontianak using Lectora Inspire. The interactive multimedia was designed based on the teacher’s interview, analysis of the current syllabus, and the English textbooks. The writer applied ADDIE as the research model. However, the writer only implemented four phases which were analyzing, designing, developing, and evaluation (ADDE). The product was designed by using Lectora Inspire and some supporting software. The contents of the interactive multimedia were focused on historical recount texts and it was adopted from “Buku Bahasa Inggris Kelas X” Version 2017 that linked to syllabus and learning objectives. The interactive multimedia was completed with some interactive features like feedbacks, navigation buttons, and dictionary. The writer used expert validation to evaluate the product based on the content aspects and the design aspects. It revealed that the product validation ranged from good to very good. Therefore, the interactive multimedia was usable to support teaching and learning processes in MAN 2 Pontianak.